Female-perpetrated sexual abuse: a review of victim and professional perspectives - Clements, Hannah; Dawson, David L.; das Nair, Roshan (Taylor & Francis, 2013)
Professional attitudes towards female-perpetrated sexual abuse (FPSA) reportedly reflect the gender-role expectations found in broader society, which cast males almost exclusively as sexual aggressors or willing sexual recipients, females as sexually non-coercive or victims and male perpetrated sexual abuse as particularly significant or injurious. Such views, however, appear to stand in contrast to the perspectives of individuals who have experienced FPSA. This paper details a systematic review of peer-reviewed quantitative and qualitative literature examining these different (professional and victim) perspectives. Although the methodological shortcomings of primary papers limit the conclusions that can be drawn, the findings suggest that victim and professional perspectives of FPSA remain discrepant; professionals generally considered FPSA as less serious, less harmful and less deserving of investigation than male-perpetrated abuse; while victims of FPSA felt their experiences influenced significantly their psychological wellbeing and abilities to form and maintain interpersonal relationships. These findings are discussed in relation to professional practice and suggestions for future research.